Bibliometry of the Revista de Biología Tropical / International Journal of Tropical Biology and Conservation: document types, languages, countries, institutions, citations and article lifespan - Monge-Nájera, Julián (2016)
The Revista de Biología Tropical / International Journal of Tropical Biology and Conservation, founded in 1953, publishes feature articles about tropical nature and is considered one of the leading journals in Latin America. This article analyzes document type, language, countries, institutions, citations and for the first time article lifespan, from 1976 through 2014. We analyzed 3 978 documents from the Science Citation Index Expanded. Articles comprised 88 % of the total production and had 3.7 citations on average, lower than reviews. Spanish and English articles were nearly equal in numbers and citation for English articles was only slightly higher. Costa Rica, Mexico, and the USA are the countries with more articles, and the leading institutions were Universidad de Costa Rica, Universidad Nacional, Universidad Nacional Autónoma de Mexico and Universidad de Oriente (Venezuela). The citation lifespan of articles is long, around 37 years. It is not surprising that Costa Rica, Mexico, and Venezuela lead in productivity and cooperation, because they are mostly covered by tropical ecosystems and share a common culture and a tradition of scientific cooperation. The same applies to the leading institutions, which are among the largest Spanish language universities in the neotropical region. American output can be explained by the regional presence of the Smithsonian Tropical Research Institute and the Organization for Tropical Studies. Tropical research does not have the rapid change typical of medical research, and for this reason, the impact factor misses most of citations for the Revista, which are made after the two-year window used by the Web of Science. This issue is especially damaging for the Revista because most journals that deal with tropical biology are never checked when citations are counted for by the Science Citation Index.